(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article the features of the organization of terminological subsystem Ukrainian language, which serves the scope of financial law defines the place of the terms of financial law in the lexical system of modern Ukrainian language and its role in shaping modern language picture of the world, analyzes the features of the organization and systematization of lexical items – financial and legal terms.